Sequence analysis of a cDNA clone encoding the C-terminal end of human complement factor H. Issue 3 (March 1987) - Day, A. J.; Ripoche, J.; Lyons, A.; McIntosh, B.; Harris, T. J. R.; Sim, R. B.
Abstract : Peptide sequencing of the complement system regulatory protein, factor H, permitted the synthesis of a mixed sequence oligonucleotide probe. Human liver cDNA libraries were screened and factor H-specific clones selected. No full-length clone was obtained, but the largest available clone, R2a, was found to encode the C-terminal 657 amino acids of factor H. The derived amino acid sequence consists of 10 contiguous internally homologous segments, each about 60 amino acids long. Sequences homologous to these are found in several other complement and non-complement proteins. Such sequences are likely to represent a particular type of tertiary structure subunit.